Inhibition of gene expression by triple helix-directed DNA cross-linking at specific sites. - Grigoriev, M (1993)
Synthetic oligodeoxynucleotides represent promising tools for gene inhibition in live systems. Triple helix-forming oligonucleotides, which bind to double-stranded DNA, are of special interest since they are targeted to the gene itself rather than to its mRNA product, as in the antisense strategy. Triple helix-forming oligonucleotides can be coupled to DNA-modifying agents and used to introduce modifications in the DNA target in a highly sequence-specific manner. We have recently designed psoralen-oligonucleotide conjugates, which, upon binding to double-stranded DNA sequences via triple helix formation, may be cross-linked in vitro to both strands of the DNA following UV irradiation. A psoralen-oligonucleotide conjugate was targeted to the promoter of the alpha subunit of the interleukin 2 receptor (IL-2R alpha) gene. The triple helix site overlaps the binding site for the transcription factor NF-kappa B, which activates transcription from the IL-2R alpha promoter. After UV irradiation, the oligonucleotide conjugate becomes cross-linked to the target site and inhibits transcription of reporter plasmids transfected in live cells. Inhibition is observed when UV-induced cross-linking occurs both in vitro (before transfection) and in vivo (after transfection). We directly demonstrate that this inhibitory effect is due to triple helix formation at the target site, since a mutant of the promoter, to which oligonucleotide binding was inhibited, was not affected by the psoralen-oligonucleotide conjugate after UV irradiation. In addition, we demonstrate that site-specific cross-linking upstream of the promoter has no effect on transcription.